Cultural Perspectives on Millennials - Berger, Arthur Asa (Springer International Publishing, 2018)
This book provides a cultural studies analysis of Millennials and their impact on American culture and society. Beginning with an introduction that touches upon which part of the population is described as Millenial, the book also explores the Millennial psyche, marketing to Millennials, Millennials' purchasing preferences, gender and sexuality among Millenials, and Millenials and their relation to postmodernism, among other things. Cultural Perspectives on Millenials is designed for students taking courses in cultural studies, sociology, American studies and related fields. It is written in an accessible style and makes use of numerous quotations from writers and thinkers who have written about Millennials. It is illustrated by the author. Arthur Asa Berger is Professor Emeritus of Broadcast and Electronic Communication Arts at San Francisco State University, USA. He is author or more than one hundred articles and seventy books on media, popular culture, humor, and tourism.